Successful management of multiple-systemic Langerhans cell histiocytosis involving endocrine organs in an adult: A case report and review of literature. Issue 26 (June 2018) - Xie, Junhui; Li, Zhen; Tang, Yi
Abstract: Rationale: Langerhans cell histiocytosis (LCH) involving non-endocrine organs has been frequently reported, whereas LCH involving endocrine organs is rare and the mechanism is unclear. Patient concerns: We report a case of multiple-systemic Langerhans cell histiocytosis (LCH) that first manifested with thyroid goiter, followed by pituitary and liver involvement. Diagnoses: The diagnosis was confirmed based on immunohistochemistry of the thyroid and liver. Interventions: The patient was treated with thyroidectomy combined with chemotherapy and radiation therapy for thyroid and liver, respectively. Outcomes: Surprisingly, the patient presented with clinical remission and no new lesion of LCH was found during follow-up over 10 years. Lessons: LCH involving the endocrine system is unusual and easily misdiagnosed or delayed, especially when the thyroid and pituitary glands are involved. Pathological examination is necessary for a definitive diagnosis. Regular examinations, such as anterior and posterior pituitary hormones, should be especially evaluated annually in the patients with LCH involving endocrine system.